Factor Influencing to Prevention of COVID-19 Infection among the Older Adults in Chaiyaphum Province - Napattaradechanon, Khemika; Phattharasirisomboon, Phakwarin; Pronlerttaveekun, Sutapinun (Journal of The Royal Thai Army Nurses, 2024)
This research is a descriptive research was to analyze the factors that influenced the prevention of COVID-19 in older adults in Chaiyaphum Province. The sample group is 422 older adults living in Chaiyaphum Province. Data were collected using a general information questionnaire. Questionnaire on factors influencing health promotion behavior to prevent COVID-19 infection and health promotion behavior questionnaire to prevent COVID-19 infection. Data were analyzed using Pearson’s correlation coefficient and stepwise multiple regression. The study results showed that older adults have health promotion behaviors to prevent COVID-19 infection at a good level (M = 3.73, SD = 27). Situational influences (Beta = 0.59, t = 10.98, p <.001), perceived benefits of practice (Beta = -0.13, t = -2.85, p = .005), and interpersonal influences (Beta = 0.10, t = 1.98, p = .04) were able to predict the health promotion behaviors to prevent COVID-19 infection of the older adults at 37.6 percentages (R2 = .376, F = 83.86, p < .001). The factors that most affect the prevention of COVID-19 among the older adults in Chaiyaphum Province is influenced by the situation (Beta = 0.59, t = 10.98, p <.001) Recommendation: It can be used as basic information for experimental research to develop health promotion skills in preventing COVID-19 infection related to factors influenced by the situation. Perceived benefits of practice and the interpersonal influence of the older adults in the area.